Thoughts in the Field: 'Self-reflexive narrative' in field recording. Issue 3 (11th November 2016) - Anderson, Isobel; Rennie, Tullis
Abstract : This article considers the presence of 'self-reflexive narrative' in field recording. The authors interrogate a common presumption within sonic arts practice and sound studies discourse that field recordings represent authentic, impartial and neutral documents. Historically, field recording practice has not clearly represented narratives of how, when, why and by whom a field recording is made. In contrast, the social sciences have already experienced a narrative 'turn' since the 1970s, which highlighted the importance of recognising the presence and role of the researcher in the field, and also in representations of fieldwork. This provides an alternative framework for understanding field recording, in considering the importance of the recordist and their relationship with their recordings. Many sonic arts practitioners have already acknowledged that the subjective, personal qualities of field recording should be embraced, highlighted and even orated in their work. The authors' own collaborative project Thoughts in the Field further explores these ideas, by vocalising 'self-reflexive narratives' in real time, within field recordings. The authors' collaborative composition, Getting Lost (2015), demonstrates the compositional potentials this approach offers.